The Effect of Training and Development, Career Development with the Mediation of Organizational Commitment on Employee Performance of Generation Z Employees in Jakarta - Benedicta Terra Pramudiana; Daniel Ong Kim Kui (Dinasti International Journal of Digital Business Management, 2026)
This study aims to analyze the influence of Training and Development, Career Development, and Organizational Commitment on the Performance of Generation Z Employees in Jakarta. This study uses a quantitative method with a survey approach using a questionnaire to 270 respondents. The analysis was conducted using PLS-SEM to test direct and mediation relationships. The results of the study indicate that Career Development and Organizational Commitment have a positive and significant effect on Performance, while Training and Development does not show a significant direct effect. Furthermore, Organizational Commitment is proven to mediate the relationship between Training and Development and Career Development on Employee Performance. These findings provide insight that improving the Performance of Generation Z requires clear Career Development support and strengthened by Organizational Commitment